2023
DOI: 10.3389/fmed.2023.1260943
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for the diagnosis and treatment of knee osteoarthritis with integrative medicine based on traditional Chinese medicine

Lingfeng Zeng,
Guanghui Zhou,
Weiyi Yang
et al.

Abstract: Knee osteoarthritis (KOA) is a common geriatric disease in middle-aged and elderly people. Its main pathological characteristics are articular cartilage degeneration, changes in subchondral bone reactivity, osteophyte formation at joint edges, synovial disease, ligament relaxation or contracture, and joint capsular contracture. The prevalence rate of symptomatic KOA in middle-aged and elderly people in China is 8.1%, and this is increasing. The main clinical manifestations of this disease are pain and limited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 76 publications
0
10
0
Order By: Relevance
“…Thus, in our case, pain and discomfort seem not to be the major cause of alarm for patients, but rather the affectation of joint elasticity. A recent study confirmed that the incidence of pain and tenderness in the case of KOA is 36.8-60.7%, this being most often accompanied by limited activity, joint deformities, bone rub feeling, and muscle atrophy [25].…”
Section: Discussionmentioning
confidence: 86%
“…Thus, in our case, pain and discomfort seem not to be the major cause of alarm for patients, but rather the affectation of joint elasticity. A recent study confirmed that the incidence of pain and tenderness in the case of KOA is 36.8-60.7%, this being most often accompanied by limited activity, joint deformities, bone rub feeling, and muscle atrophy [25].…”
Section: Discussionmentioning
confidence: 86%
“…Notably, during stair ascent, there was a decrease in overall stair gait velocity compared to stair descent (F (1,24) =30.411, P<0.001). Additionally, step width was greater during stair descent compared to ascent (F (1, 24) =4.013, P=0.039), while no significant differences were observed for step length (F (1, 24) =0.792, P=0.318) and stride length (F (1, 24) =0.344, P=0.571) between the two directions.…”
Section: Resultsmentioning
confidence: 99%
“…In terms of stair descending, the KOA group displayed distinct stair gait characteristics compared to the control group. They exhibited shorter step length (F (1, 24) =6.002, P=0.019), wider step width (F (1, 24) =4.623, P=0.029), shorter stride length (F (1,24) =6.098, P=0.022), reduced time in single-support time (F (1, 24) =5.551, P=0.011), increased time in doublesupport time (F (1, 24) =7.875, P=0.009), prolonged total support time (F (1, 24) =9.862, P=0.003), and lower veloc-ity (F (1, 24) =18.509, P<0.001). Similarly, during stair ascending, the KOA group also demonstrated significant differences compared to the control group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 18 Guidelines for the diagnosis and treatment of KOA with integrative medicine based on TCM concluded that KOA can be divided into the following syndrome types: dampness‐cold obstruction syndrome, dampness–heat obstruction syndrome, qi‐blood stagnation syndrome, deficiency in liver and kidney, and qi‐blood weakness syndrome. 108 TCM is effective in the prevention and treatment of KOA, and the adverse reactions are minimal, and patient compliance is high; compared with side effects like trauma and high cost of Western medicine treatment of KOA, TCM has many unique advantages. As a traditional treatment method, Chinese medicine compounds have shown certain efficacy in alleviating knee pain, reducing inflammation, and improving knee joint function.…”
Section: Conclusion and Prospectmentioning
confidence: 99%